Karakteristik Kimia Makanan Jajanan Berbahan Dasar Sagu (Sagu lempeng, Sagu Tumbu, Sarut, Bagea, Kue bangket) - Palijama, Syane; Lawalatta, Petranes; Polnaya, Febby J (Universitas Pattimura, 2025)
This study aimed to analyze and determine the chemical characteristics of various sago-based snacks. A completely randomized design was employed with five treatments: sago tumbu, sarut, kue bangket, bagea, and sago lempeng, each replicated three times. The parameters observed included moisture content, ash content, protein content, fat content, and reducing sugar content. The results indicated that sago flakes contained 12.68% moisture, 0.13% ash, 0.19% protein, 0.04% fat, and 0.09% reducing sugar. Sago tumbu exhibited 9.47% moisture, 0.19% ash, 3.99% protein, 15.79% fat, and 23.56% reducing sugar. Sarut contained 3.98% moisture, 0.29% ash, 1.33% protein, 9.28% fat, and 5.46% reducing sugar. Bagea showed 6.67% moisture, 0.16% ash, 3.29% protein, 9.86% fat, and 0.23% reducing sugar. Meanwhile, kue bangket had 3.26% moisture, 0.21% ash, 7.17% protein, 27.23% fat, and 11.33% reducing sugar. These findings highlight the diversity of chemical compositions among sago-based snacks, which may influence their nutritional value and potential applications in food product development.